Temporal regulation of the Mediator complex during muscle proliferation, differentiation, regeneration, aging, and disease - Kolonay, Dominic W.; Sattler, Kristina M.; Strawser, Corinne; Rafael-Fortney, Jill; Mihaylova, Maria M.; Miller, Katherine E.; Lepper, Christoph; Baskin, Kedryn K. (Frontiers in Cell and Developmental Biology, 2024)
Genesis of skeletal muscle relies on the differentiation and fusion of mono-nucleated muscle progenitor cells into the multi-nucleated muscle fiber syncytium. The temporally-controlled cellular and morphogenetic changes underlying this process are initiated by a series of highly coordinated transcription programs. At the core, the myogenic differentiation cascade is driven by musclespecific transcription factors, i.e. the Myogenic Regulatory Factors (MRFs). Despite extensive knowledge on the function of individual MRFs, very little is known about how they are coordinated. Ultimately, highly specific coordination of these transcription programs is critical for their masterfully timed transitions, which in turn facilitates the intricate generation of skeletal muscle fibers from a naïve pool of progenitor cells. The Mediator Complex links basal transcriptional machinery and transcription factors to regulate transcription and could be the integral component that coordinates transcription factor function during muscle differentiation, growth, and maturation. In this study, we systematically deciphered the changes in Mediator Complex subunit expression in skeletal muscle development, regeneration, aging, and disease. We incorporated our in vitro and in vivo experimental results with analysis of publicly available RNA-seq and single nuclei RNA-seq datasets and uncovered the regulation of Mediator subunits in different physiological and temporal contexts. Our experimental results revealed that Mediator subunit expression during myogenesis is highly dynamic. We also discovered unique temporal patterns of Mediator expression in muscle stem cells after injury and during the early regeneration period, suggesting that Mediator subunits may have unique contributions to directing muscle stem cell fate. Although we observed few changes in Mediator subunit expression in aging muscles compared to younger muscles, we uncovered extensive heterogeneity of Mediator subunit expression in dystrophic muscle nuclei, characteristic of chronic muscle degeneration and regeneration cycles. Taken together, our study provides a glimpse of the complex regulation of Mediator subunit expression in the skeletal muscle cell lineage and serves as a springboard for mechanistic studies into the function of individual Mediator subunits in skeletal muscle.